Promoting Patriotism among Elementary School Students through Ethnomathematics: A Study on the Banten's Cultural Heritage - Wida Rachmiati; Hijatul Hana Istiqomah; Wardah Wardah (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2023)
The young generation's love and knowledge of national and local cultural valuesis an indicators of an attitude of love for the motherland. One of these characteristics can be instilled through the integration of national and local cultures in mathematics learning activities through an ethnomathematics approach. One of the provinces in Indonesia that has a lot of potential and diverse cultural characteristics is Banten. So that the ethnomathematics exploration of Banten culture is very important because it can be an alternative for developing ideas to integrate Banten culture in learning mathematics. The approach used in this research is qualitative. Data was collected through literature study and processed through reduction, presentation, and interpretation processes. The search results for various cultures in Banten include: traditional ceremonies, performing arts, traditional houses, traditional clothing, traditional weapons, folk songs, special foods, dances, musical instruments, historic buildings, and handicrafts. These cultures are potentials that can be utilized especially by SD/MI teachers in the Banten region to apply mathematics learning with an ethnomathematics approach. Of the many cultures in Banten, all of them are related to the concept of mathematics. but for the concept of mathematics for the elementary school level, there is a culture not all of which are suitable to be conveyed to students of elementary school age. Cultures that can be integrated with elementary school mathematics include traditional ceremonies, performing arts, traditional clothing, traditional musical instruments, typical food, dance, traditional houses, historic building,s and handicrafts. These cultures can be integrated as teaching materials related to the concept of counting, currency values, perimeter of flat shapes, area of flat shapes, Least common multiple ,Greatest common divisor, properties of plane figure,properties of solid figure,and scale.